Modelos de nicho ecológico, registros fósseis e o pressuposto de equilíbrio das distribuições das espécies com o clima - Guimaraes, Tulio Max de Oliveira (2014)
Understand how species are spatially distributed has been exhaustively discussed in ecology over the last decades. Recently, frameworks based on Ecological Niche Models (ENM) have emerged to avoid problems related to the lack of species geographical information, once it identify which environmental suitable conditions of geographic space enable the persistence of species. Recently this approach has become a significant component in Systematic Conservation Planning, helping managers to select better areas to create reserves. Several factors limit the fundamental niche of species and poor geographical information about species distribution may lead to be an underestimation of suitable conditions that one specie occur,, revealing an non-equilibrium with climate. Thus, using good fossil records to construct ecological niche models can be a better way to evaluate and improve ENM predictions and it allows us to estimate other suitable conditions not seen before. Thereby, our aim was to investigate if ENMs built for Mauritia flexuosa, and Tapirus terrestris improve with the addition of fossil information. So, different ENMs were built using, first, current records and, second, using different proportions of fossil data. The results showed that species closer to equilibrium with climate (M. flexuosa) had an improvement in model’s performance with the addition of fossil records, while species with higher non-equilibrium (T. terrestris) decreased the model’s performance.